Profibrotic epithelial phenotype: a central role for MRTF and TAZ - Bialik, Janne Folke (Sci Rep, 2019)
Epithelial injury is a key initiator of fibrosis but - in contrast to the previous paradigm - the epithelium in situ does not undergo wide-spread epithelial-mesenchymal/myofibroblast transition (EMT/EMyT). Instead, it assumes a Profibrotic Epithelial Phenotype (PEP) characterized by fibrogenic cytokine production. The transcriptional mechanisms underlying PEP are undefined. As we have shown that two RhoA/cytoskeleton-regulated transcriptional coactivators, Myocardin-related transcription factor (MRTF) and TAZ, are indispensable for EMyT, we asked if they might mediate PEP as well. Here we show that mechanical stress (cyclic stretch) increased the expression of transforming growth factor-β1 (TGFβ1), connective tissue growth factor (CTGF), platelet-derived growth factor and Indian Hedgehog mRNA in LLC-PK1 tubular cells. These responses were mitigated by siRNA-mediated silencing or pharmacological inhibition of MRTF (CCG-1423) or TAZ (verteporfin). RhoA inhibition exerted similar effects. Unilateral ureteral obstruction, a murine model of mechanically-triggered kidney fibrosis, induced tubular RhoA activation along with overexpression/nuclear accumulation of MRTF and TAZ, and increased transcription of the above-mentioned cytokines. Laser capture microdissection revealed TAZ, TGFβ1 and CTGF induction specifically in the tubular epithelium. CCG-1423 suppressed total renal and tubular expression of these proteins. Thus, MRTF regulates epithelial TAZ expression, and both MRTF and TAZ are critical mediators of PEP-related epithelial cytokine production.